Freedom of Religion in Islam and Human Rights - Mahyudin Ritonga; Ramza Fatria Maulana; Zulkifli; Shofwan Karim (Waraqat: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to examine the development of religious freedom in Indonesia and the relationship between human rights (HR) principles in Islam and international HR standards. According to SETARA Institute data from 2023, there has been a significant increase in violations of religious freedom, with 217 incidents and 329 violation acts, mostly perpetrated by non-state actors. Although this right is protected by the constitution and Law Number 39 of 1999, serious challenges remain. This research employs a qualitative method with a descriptive-analytical approach to explore expert perspectives on religious freedom in Islam, integrating legal document analysis, academic literature, and a comparative approach between Islamic law and international HR standards. Findings indicate that HR principles in Islam have a strong foundation through the maqasid al-shariah principles, which encompass the protection of life, religion, intellect, lineage, and property, aligning with universal HR despite distinct theological bases. In Indonesia, as a country that recognizes religious pluralism and is founded upon Pancasila, religious freedom is guaranteed through the 1945 Constitution. The study concludes that harmonizing Islamic and international HR principles in religious freedom necessitates an integrative, dialogical, and contextual approach, especially through collaboration between Muslim scholars and international HR experts. Despite ongoing challenges such as radicalism and the politicization of religion, legal reform and moderate approaches in some Muslim countries demonstrate that a synthesis between Islamic values and modern HR can be achieved with balance and inclusivity